2010
DOI: 10.3390/ma3042483
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Detoxification Therapies for Critical Care

Abstract: Toxicity resulting from prescription drugs such as tricyclic antidepressants and cardioactive steroids, as well as drugs of abuse and exposure to environmental chemicals, represents a major need for detoxification treatments. Particles and colloids, antibody fragments (Fab), and indirect treatment methods such as macroemulsions, are currently being developed or employed as detoxification therapies. Colloids, particles, and protein fragments typically mitigate toxicity by binding to the toxin and reducing its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
(116 reference statements)
0
10
0
Order By: Relevance
“…In yeast cells, lipid particles detoxify excessive amounts of lipophilic substances [51] . Even in humans, liposomes are used for detoxifying patients with overdoses of drugs, such as heroin, opioids, and cocaine [52] . The fact that the Ama-KTT/M/2 stock responds to α-amanitin with a several thousand-fold induction of lipid particle genes suggests that cytoplasmic lipid particles contribute to the resistance to α-amanitin in the Ama-KTT/M/2 stock.…”
Section: Resultsmentioning
confidence: 99%
“…In yeast cells, lipid particles detoxify excessive amounts of lipophilic substances [51] . Even in humans, liposomes are used for detoxifying patients with overdoses of drugs, such as heroin, opioids, and cocaine [52] . The fact that the Ama-KTT/M/2 stock responds to α-amanitin with a several thousand-fold induction of lipid particle genes suggests that cytoplasmic lipid particles contribute to the resistance to α-amanitin in the Ama-KTT/M/2 stock.…”
Section: Resultsmentioning
confidence: 99%
“…However, some toxins present poor affinity for charcoal (e.g., alcohols, hydrocarbons, nicotinic acid, and some metals such as iron or lithium), , reducing the efficacy of activated charcoal. Although the ability of various nanomaterials (e.g., liposomes, antibody fragments, microemulsions) to capture drugs and other toxins has been reviewed, , to date only an injectable γ-cyclodextrin (Sugammadex) has reached the clinical stage for the reversal of neuromuscular blockade induced by specific anesthetics . Consequently, there is great interest in the development of safe and effective detoxification treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The most common TCAs reported in overdose are amitriptyline, dosulepin, and imipramine (Howell and Chauhan, 2010). Poison Control Centers in the United States report TCAs as the third most reported type of poisoning.…”
Section: Drug Overviewmentioning
confidence: 99%
“…There have been cases of small human studies with mild TCA overdose that have shown success using this therapy but it is not yet approved for use in the United States and studies are continuing (Howell and Chauhan, 2010). Fab therapies have a high binding capacity for the toxin and work like Digibind in digoxin overdose.…”
Section: Clinical Pearlsmentioning
confidence: 99%